Large‐scale production, purification, and function of a tumor multi‐epitope vaccine: Peptibody with bFGF/VEGFA. Issue 9 (29th July 2020) - Zhang, Ligang; Jiang, Chengcheng; Chen, Xi; Gu, Jiangtao; Song, Qifang; Zhong, Hui; Xiong, Sheng; Dong, Qingfeng; Yu, Jin‐Chen; Deng, Ning
Abstract: In tumor tissue, basic fibroblast growth factor (bFGF) and vascular endothelial growth factor A (VEGFA) promote tumorigenesis by activating angiogenesis, but targeting single factor may produce drug resistance and compensatory angiogenesis. The Peptibody with bFGF/VEGFA was designed to simultaneously blockade these two factors. We were aiming to produce this Fc fusion protein in a large scale. The biological characterizations of Peptibody strains were identified as Escherichia coli and the fermentation mode was optimized in the shake flasks and 10‐L bioreactor. The fermentation was scaled up to 100 L, with wet cell weight (WCW) 126 g/L, production 1.41 g/L, and productivity 0.35 g/(L·h) of IPTG induction. The target protein was isolated by cation‐exchange, hydrophobic and Protein A chromatography, with total recovery of 60.28% and HPLC purity of 86.71%. The host cells protein, DNA, and endotoxin residues were within the threshold. In mouse model, immunization of Peptibody vaccine could significantly suppressed the tumor growth and angiogenesis, with inhibition rate of 57.73 and 39.34%. The Peptibody vaccine could elicit high‐titer anti‐bFGF and anti‐VEGFA antibodies, which inhibited the proliferation and migration of Lewis lung cancer cell cells by decreasing the Akt/MAPK signal pathways. Therefore, the Peptibody with bFGF/VEGFA might be used as a therapeutic tumor vaccine. The large‐scale process we developed could support its industrial production and pre‐clinical study in the future.